Whipple's Disease in a 61-Year-Old Patient. Clinical Follow-Up - Zh. G. Simonova; О. V. Pestereva; D. A. Dyakonov; М. А. Karepanov; М. S. Ralnikova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present a clinical observation of a patient with Whipple's disease, demonstrating the difficulties in diagnosing the disease.Key points. A clinical observation of Whipple's disease in a 61-year-old man is described. The onset of the disease was manifested as polyarthritis three years before diagnosis. The further course of the disease occurred during the pandemic of a new coronavirus infection COVID-19, which made the diagnostic search difficult. Clinical manifestations of fever, arthralgias, diarrhea, lymphadenopathy, anaemia and weight loss raised suspicion of Whipple's disease. Key to the diagnosis were endoscopic studies with multiple small bowel biopsies, which allowed histological identification of PAS-positive macrophages in the small bowel mucosa. Therapy with ceftriaxone for 14 days, therapy with trimethoprim-sulfamethoxazole (160 mg/800 mg twice a day) for 14 months resulted in positive clinical dynamics, improvement of laboratory parameters, disappearance of PAS-positive macrophages in the small intestinal mucosa, indicating remission of the disease.